Surnames and Patronymics Formation in Dargin Language - K. A. Yusupov (Научный диалог)
The issue of formation of Dargin surnames and patronymics, which is one of the topical problems in the onomastics of the Dargin language, is considered. Attention is paid to the history of the formation of surnames and patronymics in the Dargin anthroponymic system. The results of the research review on this topic are presented. The question of the role of the Russian language in the formation of the Dargin anthroponymic system is raised. The relevance of the study is determined by the fact that this issue has not yet been the subject of a comprehensive and in-depth analysis of researchers. Variants of Dargin names and patronymics are given - traditional and Russified, established during the period of implementation of the Russian official name model. It is proved that in the early 1930-ies in connection with the introduction of passports Dargin names and patronymics appeared, corresponding to the Russian three-member model names, which is actively used now in the Republic of Dagestan. Despite this, there is an oral existence of Dargin traditional model of the name; it is sometimes used on a letter, for example, the traditional national name can be seen in the tombstones. It is proved that this contradiction characterizing speech practice creates difficulty and requires elimination. The author speaks about the expediency of the development of the law on personal names, which can be prepared by joint efforts of linguists and legislative bodies of the Republic of Dagestan.